Conflict Management in Islamic Educational Institutions in The Era of Digital Transformation: A Systematic Literature Review - Agung Safitri; Oki Dermawan; Muhammad Anas Maarif (re-JIEM (Research Journal of Islamic Education Management), 2026)
This systematic literature review examines how conflict management enhances organizational effectiveness in Islamic educational institutions amid digital transformation. Guided by PRISMA, 15 peer-reviewed studies (2020–2025) were thematically synthesized from an initial pool of 350 records. Findings indicate that conflicts primarily stem from interpersonal, structural, and value-based dynamics. Collaborative and compromise strategies yield the most positive organizational outcomes, with transformational leadership serving as a critical mediator. This study’s novelty lies in integrating contemporary conflict theory with Islamic deliberative ethics (musyawarah), which prioritizes justice, inclusivity, and collective responsibility. However, digital-era conflict dynamics remain underexplored. Overall, constructive conflict management significantly strengthens institutional stability, trust, and educational service quality. The review proposes an integrative framework aligning conflict resolution strategies, adaptive leadership, dialogic communication, Islamic values, and digital governance. Practically, institutional leaders should institutionalize preventive, data-informed conflict systems tailored to digitally evolving environments. The study also highlights the need for standardized effectiveness metrics and longitudinal, mixed-method research to validate these dynamics. Ultimately, conflict should be reconceptualized as a strategic lever for organizational resilience and innovation in Islamic education.